THE CONTFLICT ABOUT MONUMENTS AND REMEMBRANCE SITES OR THE NEW-OLD PERCEPTION OF THE PAST IN CENTRAL AND EASTERN EUROPE AFTER 1989 - Lewicki, Jakub (Porównania, 2013)
Multicultural places and monuments can unite or divide and bring about conflict. Such new-old perception of the past and the monuments is frequent in Central and Eastern Europe after 1989. In contrast, work on the protection and preservation can be an idea that unites different communities, creates bridges and new bonds. At present, it is not only the monuments which unite but the work to maintain and preserve them which constitutes a common goal. This tendency is contrary to the postcolonial perception of the world. The work describes the multiculturality of monuments paying attention to the mobility of artists, works of arts and borders. Also, an analysis of the issue of uni-, bi- and multicultural heritage ownership is offered.